Implementation of Competency Based Education through Blended Learning approach in TVET sector of Pakistan: Critical Analysis using Literature Review - Ahmed, Zamir; Alwi, S. Khurram Khan; Akhtar, Rana Naeem (Pakistan Journal of Humanities and Social Sciences, 2022)
The teaching and learning process (TLP) has been reshaped in a timely manner as per need, for better understanding. Technical and Vocational Education & Training is one of the main sectors, delivering education and training simultaneously for the socio-economic development of every nation. The sector has been facing different types of challenges in different contexts. Competency Based Training and Assessment is one of the major domains, to maintain the demand and supply ratio of the market to cover the need. The normal delivery of TLP is interrupted when COVID – 19 pandemic situation occurs. To ensure the delivery of TLP in the situation blended approach was introduced to carry on the process without any disturbance, whereas the underdeveloped countries suffered from the pandemic, due to multiple issues. This research article covers the different scenario, and find out the gaps in the proposed conceptual framework that the disbalancing of developed and underdeveloped countries would be maintained. After finding, recommendations were also made that there is an acute need for online, offline, and face-to-face approaches for teaching and learning along with the transformation of Competency-Based Education (CBE) in the TVET sector of Pakistan to live, with sustainability and also for socio-economic development.